Construcción de una red de turismo comunitario en la parroquia de Simiátug, cantón Guaranda, provincia Bolívar - Ramos Sigcha, Juanito (2014)
In this paper the problem of graduation community tourism is discussed in Simiátug Parish Canton Guaranda (Bolívar), from the perspective of the social economy. To do the tourist inventory of the five communities with the greatest tourist potential resents the parish, and through semi-structured interviews, applied to community tour guides, leaders and entrepreneurs involved in tourism, problems and strengths that are identified each. Finally some recommendations on how to strengthen the community sector are made in the parish